1998
DOI: 10.1161/01.hyp.32.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Nitric Oxide to Reactive Hyperemia

Abstract: Abstract-Our objectives were to (1) test the hypothesis that nitric oxide (NO) contributes to peak reactive hyperemia (RH) in the human peripheral vasculature, (2) examine the impact of atherosclerosis and its risk factors on RH, and (3) investigate whether L-arginine will improve RH in patients with endothelial dysfunction. The endothelium contributes to shear stress-mediated vasomotion by releasing a variety of dilating factors, including NO, but the contribution of NO to peak RH in patients with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
1
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 73 publications
3
103
1
5
Order By: Relevance
“…hyperemia is also altered in hypertension, with reduction of both peak and AUC, there is no change of the kinetic parameters of the response (Dakak et al, 1998). Thus, although hypertension is a major risk factor for small artery diseases, the corresponding patterns of the skin microvascular reactivity are distinct from CADASIL.…”
Section: Discussionmentioning
confidence: 97%
“…hyperemia is also altered in hypertension, with reduction of both peak and AUC, there is no change of the kinetic parameters of the response (Dakak et al, 1998). Thus, although hypertension is a major risk factor for small artery diseases, the corresponding patterns of the skin microvascular reactivity are distinct from CADASIL.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, moreover, insulin has been shown to stimulate vasodilatory effects by inducing endothelial nitric oxide (NO) production [21]. The idea that NO plays a part in intramuscular reactive hyperaemia is supported by most [22,23,24], but not all studies [25] using venous occlusion plethysmography. Therefore, in the present study, enhanced endothelial NO production might have contributed to insulin-mediated changes in intramuscular reactive hyperaemia.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Estimates of endothelial function by this test are remarkably stable over time, but no clear set of normal values has been developed. 7 Because of the different genetic background and variability in the distribution of CVD risk factors, normal values of FMD may differ among populations.…”
Section: Endothelial Function and Cardiovascular Diseasementioning
confidence: 99%
“…8,10 An important body of evidence suggests that endothelial dysfunction is a generalised process that is not necessarily confined to vessels with overt atherosclerotic alterations. [4][5][6][7][8][9][10] This proposal is strengthened by the high correlation (Ͼ0.75) reported between the coronary vasomotor response and the peripheral endothelial function of the brachial artery evaluated by FMD. 11,12 Recently, three different groups 10,13,14 have demonstrated that the diagnostic of endothelial dysfunction realised in coronary and peripheral arteries in patients with different stages of coronary artery disease is related with an increased incidence of an adverse long-term outcome of coronary heart disease.…”
Section: Endothelial Function and Cardiovascular Diseasementioning
confidence: 99%